2014
DOI: 10.1177/009164711404200402
|View full text |Cite
|
Sign up to set email alerts
|

Attachment to God, Psychological Need Satisfaction, and Psychological Well-Being among Christians

Abstract: Human attachment relationships are considered to be foundational to psychological well-being (Fonagy, 1999; Warren, Huston, Egeland, & Sroufe, 1997) and, by extension, attachment to God is often considered foundational to psychological well-being amongst Christian believers (Kirkpatrick, 1999; Miner, 2009). However, studies of psychological need satisfaction by different attachment figures (La Guardia, Ryan, Couchman, & Deci, 2000) suggest that experiences in which basic psychological needs are satisfied are c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 54 publications
1
11
0
Order By: Relevance
“…Although study findings show evidence of the links between RS and QoL in medical-health research for the last decade, we were unable to retrieve some studies related to RS and QoL during our initial literature search due to indexing problems and date of publication. After conducting a manual search of related articles reporting on the links between RS and QoL, we found some related studies (e.g., [ 16 , 37 , 79 83 ]), but were not able to report them because they were either not indexed in the selected databases (i.e., PubMed, ScienceDirect, and PsycINFO), using a different conceptualisation of QoL (e.g., levels of emotional distress), or were published after our deadline of literature search (i.e., March 2017). However, the results from these “missing” studies also support the salutary effects of an attachment-based model of RS on levels of psychological wellbeing.…”
Section: Discussionmentioning
confidence: 99%
“…Although study findings show evidence of the links between RS and QoL in medical-health research for the last decade, we were unable to retrieve some studies related to RS and QoL during our initial literature search due to indexing problems and date of publication. After conducting a manual search of related articles reporting on the links between RS and QoL, we found some related studies (e.g., [ 16 , 37 , 79 83 ]), but were not able to report them because they were either not indexed in the selected databases (i.e., PubMed, ScienceDirect, and PsycINFO), using a different conceptualisation of QoL (e.g., levels of emotional distress), or were published after our deadline of literature search (i.e., March 2017). However, the results from these “missing” studies also support the salutary effects of an attachment-based model of RS on levels of psychological wellbeing.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have found that attachment is linked to psychological needs, which are correlated with FOMO. Specifically, both attachment anxiety and avoidance have been related to satisfying basic psychological needs (LaGuardia et al, 2000;Wei et al, 2005;Felton and Jowett, 2013;Miner et al, 2014). Other studies found that both anxious and avoidant attachment dimensions positively predicted basic psychological need satisfaction (Wei et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…In a sample of Chinese Christians living in America, Wei, Ku, Chen, Wade, Liao, and Guo, (2012) found secure attachment to God to be positively correlated with life satisfaction and positive affect. In one sample of adult Australians, Miner (2009) found attachment to God to be positively associated with existential well-being and negatively related to anxiety, and in a second sample of adult Australians, Miner, Dowson, and Malone (2014) found God attachment anxiety to be positively correlated with stress, and both God attachment anxiety and God attachment avoidance to be positively correlated with depression and anxiety.…”
Section: Attachment To Godmentioning
confidence: 99%